Performance analysis of packet cooperative relaying system and the effect of packet length on performance - Shao-yang LIU; Yong XI; Ying LI; Ji-bo WEI; LISTERBurr A (Tongxin xuebao)
The packet error rate(PER)of the packet cooperative relay system for both(amplify-and-forward)and DF(decode-and-forward)schemes in the high signal-to-noise ratio(SNR)region was analyzed,and the effect of packet length on PER performance was studied.It is shown that both AF and DF achieve the same diversity gain in terms of PER,but with different coding gains depending on packet length.Different from the prior research,if considering prac-tical packet lengths,the DF scheme always achieves better performance than the AF scheme,with shorter packet length,the advantage of DF over AF is more obvious.For large enough packet length,AF performance approaches that of DF.It is also found that the optimal relay will always be located in the middle of the two nodes for AF regardless of packet length,while for DF,when packet length becomes large,the optimal relay moves from close to the source towards the midpoint.